Gathering up the Social: Nightlife Columns in the African-American Press - Straw, Will (Ethnologies, 2022)
In the 1920s, the modern “nightlife” column emerged as a regular feature of metropolitan newspapers in the United States and other countries. This article looks at nightlife columns in the African-American press. Its central focus is the coverage of the urban night in the Inter-State Tattler, a weekly periodical published in Harlem between 1922 and 1932. It suggests that, in the African-American press more generally, during this period, one sees the emergence of many of the varieties of the nightlife column. This emergence is particularly evident in the writing of the journalist Geraldyn Dismond, whose writing is a central focus of the article.